Dualisme Pajak di Jawa: Administrasi Pajak Tanah di Wilayah Vorstenlanden pada Masa Kolonial, 1915–1942 - Abdul Wahid (Universitas Gadjah Mada, 2017)
Land tax (landrent) was first introduced by British Ruler, Thomas Raffles in 1811/1812, but was later retained by the Government of the Dutch East Indies until the end of its power in 1942. The long history of applying this tax has led to various dynamics from continuous administrative reforms to socio-political resistance from the taxpayer (community). In general, the application of land tax adapted to local economic and political conditions to make it work effectively and efficiently. In the autonomous region of vorstenlanden, the application of land tax became the pull out field of political authority between the Dutch East Indies Colonial Government and the traditional Governments of the Yogyakarta and Surakarta palaces, both of which share political and administrative powers in their respective territories. On the one hand this condition leads to dualism administrative, because the land tax operates as a central tax and local tax, thus potentially causing double tax burdens for local communities. This article seeks to critically examine how the pull out of land tax administration in vorstenlanden and how far the tax became part of the political relations of the colonial state with the indigenous traditional state.